On ‘small’ structures in syntax: small clauses, nonsententials, and small nominals (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
This paper is concerned with various dimensions of the ‘smallness’ of syntactic structures. Grammatical constructions selected to illustrate the apparent smallness in syntax include small clauses, nonsententials and small nominals. The ‘smallness’ of small clauses (e.g. We consider him very silly) has recently drawn the attention of researchers, leading to various accounts of their internal composition and derivation. As regards small nominals, they are discussed on the basis of Pereltsvaig [2006]. It is also proposed that NPN structures (e.g. day after day) constitute an instance of ‘small’ structure. Recent developments in syntactic theory (e.g. Citko 2008; Haïk 2013; Progovac et al. 2006; Travis 2001; Pskit 2012, 2015) demonstrate that behind the surface ‘smallness’ of the above-mentioned types of expressions there are complex syntactic mechanisms.